Management and Development of Indonesia’s Economic Diplomacy in 2015-2022 in Facing Global Economic Crisis - Chairunnisa, Rizqi Shafira; Wiswayana, Wishnu Mahendra (Poltanesa, 2023)
Global uncertainty causes uncertain developments in the world economy. Various issues of the global economic crisis threaten various countries. Realizing this, Indonesia, through the Strategic Plan of the Ministry of Foreign Affairs, has begun to make efforts to maintain the stability of the country's economy by focusing its foreign policy direction on economic diplomacy. This research will try to analyze typology mapping of Indonesia's economic diplomacy to identify the management of Indonesia's economic diplomacy as an effort to improve the practice of economic diplomacy. This study uses a qualitative approach with thematic analysis methods and data collection techniques with documentary research and internet-based research. This research uses the Typology of economic diplomacy Rana because it can identify the capacity management of Indonesia's economic diplomacy as a developing country. This article shows that Indonesia has progressed well in carrying out economic diplomacy and has entered an evolving phase in the majority. This shows that the management of Indonesian Diplomacy has adapted to the opportunities that exist in carrying out its economic diplomacy. This article also finds that Indonesia is still on niche-focused typology that means Indonesia focus on carrying out economic diplomacy in certain parts and has not yet begun to open its market to other potentials. Finally, Indonesia has reached the initiative in the regional category which shows that Indonesia already has an influential role at the regional level.